(untitled) (Superficies y Vacío, 2014)
Recently, it has been reported that TiO2 with mixture of phases (anatase/rutile) exhibit higher photocatalytic activity than TiO2 with pure anatase phase. Therefore, the production and correct quantification of the ratio of phases becomes an important task. In this work, anatase TiO2 thin films were obtained by the DC reactive magnetron sputtering technique. TiO2 with mixture of phases (anatase/rutile) were prepared by thermal annealing of the as-deposited thin films. The value of the anatase/rutile ratio in the titanium dioxide thin films was estimated using Raman spectroscopy. Additionally, it is reported the dependence of the bandgap of the TiO2 thin films as a function of the anatase/rutile ratio. The band gap of the TiO2 thin films was determined from diffuse reflectance measurements.